Generative artificial intelligence and risk at work: an inevitable consequence? - Azizan Morshidi; Noor Syakirah Zakaria; Rizal Zamani Idris; Mohammad Ikhram Mohammad Ridzuan; Sitinurbayu Mohd Yusoff (Asian Scholars Network, 2023)
For quite some time, however, the interest in artificial intelligence (AI) has became very high. Generative AI being a recent development signifies another era with profound empirical queries related to work and human being. There is a need to understand how generative AI affects work, and it requires some knowledge. Though there are limited studies conducted about it, this article addresses the possibility that, through this technology, workers may face potential risks at work. The paper explores major risks associated with this technology by undertaking a literature review from credible sources such as academic journals, articles and news articles. This paper offers crucial guidance concerning the right steps organisations can take toward efficiently integrating generative AI in their organisation operations through an examination of the inherent risks involved.